Sugerir un sistema de costos adecuado para el cultivo de café de acuerdo a la cosmovisión del Resguardo indígena de Ricaurte, Paez, Cauca (2020)
The indigenous reserve of Ricaurte, Páez, Cauca has cultivated coffee for more than a century, this bean is the main source of income for the community, which has been cultivated under the indigenous worldview, which means “Way of seeing the world”, for what the community assures that it has special characteristics due to these practices, during this time, the coffee farmers have carried out the cost analysis empirically, as a consequence of this the utility or loss of this activity is not known for certain, which is why which the main objective of this research is to identify the ideal cost system according to the needs and conditions of this agricultural process, where the first step will be to learn the worldview of this community against coffee production, then study and contextualize the step by step of the process carried out to grow coffee and, finally, of the existing cost systems, identify and exemplify which is indicated for the coffee production process of the Indigenous reservation, which will allow concluding some questions such as, if the costs are being logical and proportional, as well as determining the final cost of the coffee load, the percentage of profit that the coffee growers obtain once they are It has commercialized the grain and the time of return of the investment.